Tinjauan Teologis Tentang Ibadah Bagi Pelaksanaan Misi Allah - Yonatan Sumarto (Sekolah Tinggi Theologia Jaffray, 2019)
This paper aims to explain the theological review of worship for the implementation of God’s mission. The method used is descriptive qualitative with literature review. The conclusion is that worship is worshiping the Lord God as well as testing missionary actions of the church members. Worship moves God's people to experience an encounter with God, and His will. The response of God's people is to carry out God's mission for the world. Integrity of worship is knowing God's will for His mission in the world through the church, and believers.